Triticum aestivum L. subsp. aestivum CWI 7065 ... - GLIS Of The ITPGRFA (Centro Internacional de Mejoramiento de Maíz y Trigo, 2017)
Plant Genetic Resource. Taxonomy: Triticum aestivum L. subsp. aestivum Common name(s): Wheat Other names: SAKHALIN LUTESCES 22 Conserved by: Centro Internacional de Mejoramiento de Maíz y Trigo (CIMMYT), Mexico Local sample unique identifier: CWI 7065 Method of creation: Acquisition Date: 1988 Other identifiers: n/a,CWI7065, n/a,CID 271170 SID 0, n/a,PI 182529, n/a,GID 286593 Historical: No Biological status: Breeder's line MLS status: Included ...